Polyclonal activation of rat splenic lymphocytes after in vivo administration of Mycoplasma pulmonis and its relation to in vitro response. - Williamson, J S (1986)
The plaque-forming cell (PFC) assay with sheep erythrocytes (SRBC) sensitized with different antigens and a 4-h tritiated thymidine pulse assay were used to determine whether polyclonal activation occurs in rats following in vivo administration of Mycoplasma pulmonis. Injection of M. pulmonis into F344 rats resulted in an increase in the number of splenic immunoglobulin M-secreting PFC that produced antibodies reactive with the trinitrophenyl hapten and with SRBC. This polyclonal response reached a peak by 72 h after injection and returned to normal levels by 96 h, at which time the specific response to M. pulmonis reached its peak. Heat treatment and preopsonization of M. pulmonis with antiserum before injection resulted in reduced numbers of PFC against M. pulmonis-sensitized SRBC, trinitrophenyl hapten-sensitized SRBC, and SRBC. The number of PFC against the three types of target cells also increased in LEW rats after immunization with M. pulmonis. The number of PFC against SRBC and staphylococcal protein A-sensitized SRBC was higher in immunized LEW rats than in immunized F344 rats. Examination of unimmunized animals also revealed that LEW rats had higher initial numbers of PFC than did F344 rats. These results showed that polyclonal activation occurs in rats following in vivo administration of M. pulmonis and that LEW rats have an inherent propensity to develop higher nonspecific responses in vivo than F344 rats.